PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) TERHADAP HASIL BELAJAR DAN SIKAP ILMIAH SISWA PADA MATA PELAJARAN FISIKA SMA - Ernawati, Ranti; Sjarkawi, Sjarkawi; Asyhar, Rayandra (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2012)
This study was motivated by the problems faced by teachers of physics are the low daily rate of students, it is characterized by ï‚³ 50% of students are in the range of values below 60. The purpose of this experimental study is (1) reveals the presence or absence of a firmness differences in learning outcomes between students taught using cooperative learning model Group Investigation (GI) with students who are taught by using conventional learning model, (2). reveals the presence or absence of firmness is a difference of scientific attitude of students, between students taught using cooperative learning model Group Investigation (GI) with students who are taught by using conventional learning model. This study was an experimental study. The first and second hypothesis can be tested using one-way ANOVA test. Differences in the use of cooperative learning model Group Investigation (GI) with conventional learning model on learning outcomes and student scientific attitude among these variables will be known. Subjects of this study were taken randomly selected by lottery first is the X3 class numbered 40 students, was elected second lottery X5 is a class of 40 students, the class were tested for normality and homogeneity. Timing of treatment for 2 x 45 minutes (1 x meetings) that do as much as 8 times the meeting. At the end of the treatment in the final meeting of the subjects were given a final test consists of 23 multiple choice test items with time-90 minutes. Based on calculations using ANOVA one lane, with criteria if F count> F table, then H0 is rejected, meaning that there is a difference (not homogeneous), and if F count <F table, then H0 is accepted, meaning that there is no difference (homogeneous). Under these provisions, it can be interpreted that there is no difference in learning outcomes for 1.7731 <3.96. F count <F table or 1.773 <6.97 then H0 is accepted, meaning that there are no significant differences in the scientific attitude of students who use the model of cooperative learning model Group Investigation (GI) than conventional learning model The findings of this study indicate that there are differences in learning outcomes and scientific attitude of students, between students taught using cooperative learning model Group Investigation (GI), with students taught by conventional learning model. Keyword: group investigation, the results of learning, scientific attitude